Access, Resource Sharing and Collection Development, 1st edition - Lee, Sul H. (Routledge, 2020)
This book, first published in 1996, explores the role of libraries in acquiring, storing, and disseminating information in different formats to make better use of technology in sharing scarce resources and connecting library users with collections. With an expressed goal of encouraging continued debate and further investigation, this book presents developing strategies and procedures to meet the challenges faced as a collection development librarian. Among the vital concerns addressed are the competition for limited resources, trends in document delivery, access vs. ownership, the evaluation of document delivery products, and libraries’ options for the future.